Estimation of energy efficiency of kraft pulp production with the exergy increment method - Р. V. Lukanin (Известия высших учебных заведений: Проблемы энергетики)
This article contains results of exergic analysis of kraft pulping flow chart. The results of exergic balances of main kraft pulping processes such as alkali recovery at recovery boilers, black liquor evaporation, chips cooking, lime decarbonation are considered in details in the article. The analysis of the process flow chart makes it possible to determine the bottlenecks in the use of heat energy and to substantiate principal lines for increasing energy efficiency of the processes under study. A main share of the exergy expended in the existing pulping process is due to alkali recovery in the recovery boiler and comprises 70% of the total exergy available in the system. A procedure of hydrothermal production of chemicals in the process of kraft pulping is studied. A schematic diagram and analysis of heat technique of the kraft pulping process which in fact consists of organic component removal from black liquor through its autoclave carbonation with flue gases releasing from lime kiln at the temperature 80-90 oC are given in the article. The removal of organic components under these conditions can reach 70 %. In the studied version the exergic efficiency ηe = 80 % is considerably higher than that of the flow chart existing for chemicals recovery which is equal to ηe = 48 %. This is the evidence of high energy efficiency of the method developed.